Encimi vključeni v biosintezo glivnega melanina - potencialne tarče za razvoj novih antimikotikov - Brunskole Švegelj, Mojca (Farmacevtski vestnik, 2008)
Dematiaceous or dark-pigmented fungi are responsible for many infections, and especially in immunocompromised patients. Thesefungi contain melanin in their cell walls that protects them from environmental stresses and is considered tobe an important virulence factor.Infections caused by dematiaceous fungi include phaeohyphomycosis, chromoblastomyciosis and mycetoma. Despite combinedantimicotic therapies, these infections can still result in high overall mortality rates and represent an important health issue. We present here the 1,8-dihydroxynaphthalene melanin biosynthetic pathway and the enzymesinvolved. As 1,8-dihydroxynaphthalene melanin appears only in fungi, the enzymes involved in its biosynthesis represent interesting targets for thedevelopment of new selective antimicotics.
Keywords: Antifungal Agents; Antimikotiki; Biosynthesis; Dermatomikoze; Dermatomycoses; Enzymology; Fungi; fungus; Glive; Melanini; Melanins; Virulenca; Virulence